(untitled) (Theatrum historiae, 2012)
This study attempts to reconstruct the communication network established by Prince Ferdinand of Schwarzenberg in the last third of the 17th century and the early 18th century. The author analysed the aristocrat’s preserved personal correspondence and diary entries from 1687–1688 and 1696–1697 in order to outline the hierarchy of a particular nobleman’s informants, the content of mutual communication and the intents underlying the exchange of information. The peculiar features of contacts established by Ferdinand of Schwarzberg include the fact that they stretched across all social layers of the early Modern Age society: from the subjects up to members of several ruling dynasties throughout Europe.